The pluralist language ideology of Korean immigrant mothers and the English-only principle in early childhood education programs. (2nd January 2020) - Jang, Soon Young
Abstract: Canada has been largely relying on immigration for population growth. Consequently, early childhood education (ECE) programs in Canadian cities are becoming increasingly linguistically and culturally diverse. Yet, few studies have explored the experiences of immigrant families in ECE programs. This study explores the perspectives and experiences of Korean immigrant mothers in ECE programs vis-à-vis bilingualism. Through a focus group meeting and eight individual interviews, this study investigates how these mothers' language ideologies and attitudes are articulated in their discourses by asking these questions: 1) How did language play a role in the participating parents' ECE program selection?; 2) Which language do participating parents prefer for their children to acquire and what are the associated factors?; and 3) What did participating parents experience regarding educators' language views and practices? This study found that the Korean mothers hold pluralist language ideologies, expressing their desire for their children's success in and integration into the mainstream society, and for their ethnic identity and family relationship preservation. Simultaneously, the participating mothers reported the English-only principle of ECE programs, which suggests the latter's assimilationist view. The author discusses the common misconception related to this view, the maximum exposure hypothesis, and highlights implications for immigrant parents and educators.